Anther development in tribe Epidendreae: orchids with contrasting pollination syndromes - Valencia-Nieto, Benjamín; Sosa, Victoria; Márquez-Guzmán, Judith (PeerJ, 2018)
Background Epidendreae is one of the most diverse tribes among the orchids with remarkable variation in life form, floral morphology and pollination syndromes. Its circumscription was recently revised and subtribes Agrostophyllinae and Calypsoinae were transferred into this tribe. One of the principal floral characters utilized in classification of orchids is the incumbency or bending of the column. This study records and compares late stages of anther, column and lip development, and discusses anther characters in fifteen representative taxa of five of the six subtribes in Epidendreae with respect to classification and pollination biology. Methods A series of late floral stages were sampled and fixed for examination under scanning electron microscope. Results Anther incumbency or bending in this group varies from 90° to almost 180°. Incumbency in the late stages of development is reached in Bletiinae, Ponerinae, Pleurothallidinae and Laeliinae whereas incumbency is reached early in its development in Corallorhiza and Govenia of Calypsoinae. Discussion Our observations indicate that the position of Chysis in subtribe Bletiinae needs revision based on differences in a number floral, and in particular of anther characters; and that Coelia only shares the early anther incumbency with Calypsoinae members, but not the rest of floral and anther characters. Anatomical characters such as crystals around the actinocytic stomata on the anther cap and sugar crystals in Laeliinae; lack of rostellum in Bletiinae; coalescent anther with the column, lack of trichomes and papillae on lip keels, and underdeveloped rostellum in Chysis; a mechanism by which the anther cap comes off (it is joined with the grooved lip by a claw) in Isochilus are all related to pollination syndromes and reproductive biology.
Keywords: Chysis; Incumbency; Epidendreae; Anther; Development; Orchidaceae; Pollination